Happiness and environmental degradation: A global analysis - Muhammad Tariq Majeed; Shaista Mumtaz (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
This study contributes to the happiness-environment nexus by introducing the novel measures of environmental degradation such as species protection, marine protected areas and water quality unlike previous literature that mainly emphasized the importance of carbon dioxide emissions (CO2) in influencing happiness levels. The study also holds the distinction of using for the first time Environmental Performance Index (EPI) data for environmental degradation indicators. The empirical analysis is based on Ordinary Least Squares (OLS), Pooled OLS, Two Stage Least Squares (2SLS) and Generalized Method of Moments (GMM) techniques. The results suggest that CO2 emissions have strong negative impact on happiness whereas species protection and marine protected areas increase the level of happiness across the selected sample. Furthermore, economic affluence is improving the life satisfaction levels. This analysis emphasizes the need of environmental policies that aim at reducing harmful gasses such as CO2 and nitrous oxide emissions and promoting the factors like protection of bio diversities to ensure healthy functioning of environment and human society. Finally, findings of the study are shown to be robust to different specification, alternative estimation methods, and additional control variables.
Keywords: 330; happiness; environmental degradation; CO2 emissions; marine protected areas; species protection; biodiversity; water quality; nitrous oxide emissions